In vivo determination of the anti-inflammatory and antioxidant effects of the aqueous extract of Syzygium aromaticum (clove) in an asthmatic rat model: Antioxidant and anti-inflammatory effects of clove - Ounaceur, Lynda Sabrina; Messarah, Mahfoud; Lankar, Abdelaziz; Touaibia, Djihane; Ghadab , Hanene; Garri , Zohir; Boudjil, Sonia; Belkacem Djeffel , Khadidja; Atoui , Latifa; Ounaceur, Anis; Djaber, Nesrine; Boumendjel, Amel (Cellular and Molecular Biology, 2024)
Asthma is a chronic inflammatory disease of the airways strongly associated with interleukin-4 (IL-4), a cytokine that mediates and regulates various immune responses, including allergic reactions. This study aimed to evaluate the anti-inflammatory and antioxidant effects of an Aqueous Extract of Clove (AEC) Syzygium aromaticum on the lungs and erythrocytes of an experimental asthma model in Wistar rats. For this purpose, four groups of male rats were examined: control, sensitized with ovalbumin (OVA), treated with AEC, and treated with a combination of OVA/AEC. After treatment, the antioxidant effect was determined by measuring the malondialdehyde (MDA), glutathione peroxidase (GPx), glutathione (GSH), and catalase (CAT) levels. The anti-inflammatory effect was determined by measuring IL-4 levels by performing enzyme-linked immunosorbent assay (ELISA) using serum, lung, and bronchoalveolar lavage fluid (BALF) samples. A significant reduction (p ≤ 0.05) in the MDA levels and a significant increase (p ≤ 0.05) in the levels of GPx and CAT were observed in the lungs of rats treated with cloves. However, no statistically significant variation was observed in GSH levels. In erythrocytes, no statistically significant differences were observed between the experimental batches. Regarding the anti-inflammatory effect, the administration of S. aromaticum extract to sensitized rats resulted in a recovery in the levels of total proteins and IL-4 and a decrease in the three compartments studied (lungs, serum, and bronchoalveolar liquid). These results were confirmed by microscopic examination of lung histological sections. Overall, these findings confirmed that the AEC has anti-inflammatory and antioxidant effects.